"Show Me the Money!" Quantifying the Impact of Regulatory Simplification Projects - Liepina, Sanda; Dall'Olio, Andrea; Sethi, Sanwaree (World Bank, Washington, DC, 2012)
International Finance Corporation (IFC) Private Enterprise Partnership (PEP) has developed the following methodology to measure and attribute the economic impact of its national-level business enabling environment (BEE) regulatory simplification projects in Eastern Europe and Central Asia. By comparing specific aspects of the business environment before and after IFC-supported reforms are enacted by the government, it is possible to quantify the benefits accruing to the target population, i.e., the aggregate cost savings to businesses. This effort to quantify the benefits of regulatory improvements has been welcomed by both government counterparts and IFC PEP's donor partners. Using this methodology, IFC PEP has estimated an aggregate cost savings of US$84 million for businesses in its focus countries. The developed methodology is relevant throughout the project life-cycle and can be a useful tool for engaging and motivating key stakeholders to reform.